The adventures of Johnny Bunko : the last career guide you'll ever need - Pink, Daniel H. (Riverhead Books, 2008)
"Meet Johnny Bunko. He's probably a lot like you. He did what everybody--parents, teachers, counselors--told him to do. But now, stuck at a dead-end job, he's begun to suspect that what he though he knew is just plain wrong. On bizarre night, Johnny meets Diana, the unlikeliest career advisor he's ever seen. Part Cameron Diaz, part Barbara Eden, she reveals to Johnny the six essential lessons for thriving in the world of work"--P. [4] of cover.